Clinical Significance of Serum Iron in the Diagnosis of Iron Deficiency Anemia in Patients from Local Population of Punjab-Lahore - Neelum Farheen, Hina Malik, Khalida Anwar, Sara Zahid, Fatima Zahid, Ayesha Zahid, Naveed Shuja, Arif Malik (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The main cause of anemia in one-third of the world’s population is a lack of iron (ID). Anemia affects between 700 and 800 million individuals globally. Methodology: Only the patients diagnosed with iron deficiency anemia was selected from Ali Fatima Hospital Lahore and Jinnah Hospital Lahore for determination of serum iron concentration in comparison with healthy controls. Results: In our study male patients were 67% and females were 33%. Frequency of children with beta thalassemia major under 5 year of age is 19%, 5-9 year is 24%, 9-15 years is 31% and above 15 years is 26% Practical implications: The current study aims to spread the awareness among community about clinical significance of serum iron in the diagnosis of iron deficiency anemia in patients and ways to control the iron deficiency. This investigation will assist in determining the severity of the condition in our community as well as the status of serum iron levels in individuals with iron deficiency anemia. The evaluation of serum iron levels in anemic individuals will be helpful to medical experts in determining the best course of treatment. Conclusion: We concluded that renal tubular damage and hepatocellular injury may be secondary to oxidative lipid peroxidation mediated by the iron overload. However further investigations are extremely necessary for this interpretation. A better evaluation of iron toxicity and regular monitoring of renal functions, liver functions, accompanied by an improvement in chelation therapy along with the administration of selective antioxidants (vitamins E and C), may protect different organs against oxidative stress and its consequences, specifically endocrine problems. Keywords: Anemia, Iron deficiency, Ferritin, Hemoglobin, Thalassemia, hepatocellular injury.